Adaptive Backstepping Autopilot Design for Missiles of Fast Time-varying Velocity. Issue 17 (2016) - Lee, Seokwon; Kim, Youdan; Moon, Guanyoung; Jun, Byung-Eul
Abstract: An adaptive backstepping control scheme is proposed to design a missile autopilot during boost-phase. In the boost-phase, accurately controlled missiles experience fast velocity variations that make the missile dynamics be highly nonlinear. Missile parameters including the mass, the moment of inertia, and a center of gravity, which are usually considered as constants or slowly-varying, change very fast. The time-varying effects combined with nonlinear dynamics yield severe parametric uncertainties in missile dynamics. Therefore, the nonlinear dynamics as well as parametric uncertainty should be carefully treated in autopilot design. To deal with this problem, an adaptive nonlinear controller is designed based on backstepping procedure. Adaptation laws are properly designed so that robustness to the uncertainty as well as the closed-loop stability can be guaranteed using Lyapunov stability theorem. To demonstrate the performance of the proposed controller, numerical simulation is carried out.